ERRATUM TO: THE INFLUENCE OF SILICA CALCINATION TEMPERATURE VARIATION TO THE HYDROPHOBICITY AND TRANSMITTANCE ON GLASS SUBSTRATE - Rohmah, Roihatur; Zainuri, Mochamad (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2020)
Erratum: Roihatur Rohmah, M. Zainuri. Jurnal Neutrino:Jurnal Fisika dan Aplikasinya. 2020 April: 12(2):49-56. (Doi: 10.18860/neu.v12i2.8208: The title